A study on factors influencing customer satisfaction among local tourists toward budget hotels in Bandaraya Melaka / Nurfatin Kamila Arifen - Arifen, Nurfatin Kamila (Faculty of Business and Management, 2019)
The number of budget hotel in Melaka is increasing nowadays. Budget hotel that provides simple rooms and meals at lower cost has become an alternative for the customer who just wants to have a room with a bed and shower. Although there are researches examine the relationship between the SERVQUAL model and customer satisfaction in hotel industry Melaka. However, the customer satisfaction in budget hotel is seldom examined by researchers. Thus, the objective of this research is to determine the factors that affect the affecting the customer satisfaction in budget hotel Melaka. In this research, SERVQUAL model is used to identify the five dimensions that influence the customer satisfaction in budget hotel. Besides, another factor namely price will be added in this study to examine the customer satisfaction in budget hotel. Furthermore, this study will contribute significantly to the hospitality industry as the result can be used to improve the service performance of budget hotels in Melaka.